Análise das patologias da edificação da Metalúrgica Faulhaber: um contributo à conservação e preservação do patrimônio industrial - Hardt, Jeferson Grosse (2021)
The desire to keep alive the history of the city and the old building of Metalúrgica Faulhaber is noticed in several spheres of the municipality of Panambi. Historic buildings are part of the city's heritage, this is due to its important and representative architecture with the identification of the remnants of the industry, considered heritage of the city, the relevance and influence of the building for the surrounding environment and the emergence of the metal-mechanical branch of the municipality, and not only because of that, but above all as stated by Aldo Rossi, based on the “construction of the city over time, in which the city grows on itself, acquiring awareness and memory”. The research is carried out by bibliographic documental analysis and field survey, using qualitative and quantitative indicators, presenting a brief historical overview of the municipality of Panambi, questions about cultural heritage and its preservation, conservation and maintenance of historic buildings, as well as the factors of degradation in historical buildings, which will provide a foundation and detailed technical vision for the case study aiming at the correct analysis of the current state of the facades, and therefore the preparation of the damage map, with its causes and the correct therapies of the pathologies under analysis, thus managing to make a complete pathological overview of the building under study. Thus, this study is directed, or has the objective, to demonstrate the current conditions of the building, thus contributing to the conservation and preservation of the memory and history of Metalúrgica Faulhaber through the diagnosis and prognosis of the pathologies found, indicating repairs, conservation and preventive maintenance.